Changing Conceptions, Changing Practices : Innovating Teaching across Disciplines - Wardle, Elizabeth (Elizabeth Ann); Updike, Ann; Olejnik, Mandy; Martin, Caitlin; Glotfelter, Angela (Book collections on Project MUSE., 2022)
"Changing Conceptions, Changing Practices provides a theoretical lens and guide for helping groups of faculty members make deep change in their programs and departments. The work shows how institutions, divisions, programs, program leaders, and professional development leaders can help faculty engage in changing conceptions around rethinking curricula"--